2008
DOI: 10.1158/1078-0432.ccr-07-1497
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Laser-Captured Paraffin-Embedded Tissues: A Molecular Portrait of Head and Neck Cancer Progression

Abstract: Purpose: Squamous cell carcinoma of the head and neck (HNSCC), the sixth most prevalent cancer among men worldwide, is associated with poor prognosis, which has improved only marginally over the past three decades. A proteomic analysis of HNSCC lesions may help identify novel molecular targets for the early detection, prevention, and treatment of HNSCC. Experimental Design: Laser capture microdissection was combined with recently developed techniques for protein extraction from formalin-fixed paraffin-embedded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
153
0
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 44 publications
8
153
0
7
Order By: Relevance
“…In addition, among the 53 up-regulated candidates identified from the three pairs of OSCC samples used here, more than 20 candidates have been confirmed and/or rediscovered to be overexpressed in OSCC tissues using a larger number of samples in the present study or by other groups (Ref. 15 and Table I and references cited therein). This observation indicates that, although potential bias may result from using specimens from a limited number of male patients, the quantitative proteome data set generated here can be useful for searching potential OSCC biomarkers.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…In addition, among the 53 up-regulated candidates identified from the three pairs of OSCC samples used here, more than 20 candidates have been confirmed and/or rediscovered to be overexpressed in OSCC tissues using a larger number of samples in the present study or by other groups (Ref. 15 and Table I and references cited therein). This observation indicates that, although potential bias may result from using specimens from a limited number of male patients, the quantitative proteome data set generated here can be useful for searching potential OSCC biomarkers.…”
Section: Discussionsupporting
confidence: 54%
“…This study explored the relative distribution of identified proteins in tissue samples by counting the peptide numbers of each protein detected. In addition, the authors validated the expression of cytokeratins 4 and 16, desmoplakin, desmoglein 3, and vimentin proteins using immunohistochemistry (15). Although these studies identified and confirmed several OSCC/HNSCC-associated proteins, a more global view of the changes in protein expression in microdissected OSCC cells and adjacent non-tumor epithelial cells can be achieved using a precise quantification approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations